Tuesday

November 25, 2014

November 25, 2014

Posted by **Ang** on Friday, December 3, 2010 at 8:08pm.

x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1

so to produce an equation y=f(x).

**Answer this Question**

**Related Questions**

calc - eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1 so to ...

calc ii - eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1 so ...

calc ii - eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1)

Math Help please!! - Could someone show me how to solve these problems step by ...

Mathematics - sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So...

Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...

Math - How do you find a square root of a number that's not a perfect square? I'...

Inequality - When I solve the inquality 2x^2 - 6 < 0, I get x < + or - ...

MATH - I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y ...

math,algebra,help - Directions are simplify by combining like terms. x radiacal ...